2016
DOI: 10.1089/jamp.2015.1243
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Comparison of a Vibrating Mesh Nebulizer Operating in Inspiratory Synchronized and Continuous Nebulization Modes During Noninvasive Ventilation

Abstract: During simulated NIV with a single-limb circuit bilevel ventilator, the use of inspiratory synchronized vibrating mesh nebulization improves respirable dose and reduces drug loss of amikacin compared with continuous vibrating mesh nebulization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 36 publications
2
27
0
Order By: Relevance
“…Inspiration synchronized aerosol generates higher inhaled dose by reducing the waste during exhalation; this explains our findings with nebulizer placed close to patient, which agreed with the finding that higher inhaled dose with breath actuated jet nebulizer than continuous jet nebulizer when it was placed at the Y-piece during invasive ventilation [10]. Moreover, Michotte et al found higher inhaled dose with inspiration synchronized VMN than continuous VMN during noninvasive ventilation, particularly when nebulizer was placed between the single-limb ventilator and exhalation port; the waste of aerosol was more significant with continuous VMN than inspiration synchronized VMN [11]. In Golshahi et al's study, they used similar breathing parameters during quiet breathing (Vt 500 ml, RR 15) but only investigated one gas flow (20 L/min), with nebulizer placed close to patient; they also found higher inhaled dose at nostril level with inspiration synchronized than continuous aerosol [19].…”
Section: Comparison Of Inspiration Synchronized Vs Continuous Vmn Plasupporting
confidence: 68%
See 4 more Smart Citations
“…Inspiration synchronized aerosol generates higher inhaled dose by reducing the waste during exhalation; this explains our findings with nebulizer placed close to patient, which agreed with the finding that higher inhaled dose with breath actuated jet nebulizer than continuous jet nebulizer when it was placed at the Y-piece during invasive ventilation [10]. Moreover, Michotte et al found higher inhaled dose with inspiration synchronized VMN than continuous VMN during noninvasive ventilation, particularly when nebulizer was placed between the single-limb ventilator and exhalation port; the waste of aerosol was more significant with continuous VMN than inspiration synchronized VMN [11]. In Golshahi et al's study, they used similar breathing parameters during quiet breathing (Vt 500 ml, RR 15) but only investigated one gas flow (20 L/min), with nebulizer placed close to patient; they also found higher inhaled dose at nostril level with inspiration synchronized than continuous aerosol [19].…”
Section: Comparison Of Inspiration Synchronized Vs Continuous Vmn Plasupporting
confidence: 68%
“…Compared to the current commercially available continuous VMN, the inspiration synchronized VMN did not generate clinically relevant increment of inhaled dose, particularly at high gas flows. However, this finding was not surprising, as the inhaled dose was only slightly higher with inspiration synchronized VMN than continuous VMN in the previous in vitro and in vivo adult studies during noninvasive ventilation [11,12], while the inhaled dose was found to be even lower with inspiration synchronized VMN than continuous VMN during neonatal invasive ventilation in both in vitro and in vivo studies [23,24]. Additionally, all these studies found the delivery time with inspiration synchronized VMN was two-to threefold longer than continuous VMN [11,12,23,24].…”
Section: Clinical Implicationmentioning
confidence: 64%
See 3 more Smart Citations